Inclusive leadership in management - Oleg S. Vikhanskiy; Araksya G. Mirakyan; Anastasia S. Dosaeva (Управленец)
One of the current trends in management is active transformation and differentiation of approaches to business management, in particular, to interpreting the concept of leadership. The purpose of the study is to find out, through com parative analysis of leadership theories, whether inclusive leadership is a distinct concept and establish its fundamental char acteristics. The foundation of research resides in positive ethical concepts of leadership. General scientific methods (synthesis, analysis, induction, and deduction) and the dialectical method are used. The evidence base covers organizational practices of the largest companies implementing diversity and inclusion policies. Our analysis revealed the distinctive features of in clusive leadership (providing employees with equal opportunities to participate in the organization’s activities, emphasizing the uniqueness of each employee, a high level of emotional and cultural intelligence, the ability to manage a diverse team and benefit from it, etc.) as well as its characteristics (openness, the ability to listen and hear, etc.) shared with other types of leadership (servant, participatory, etc.). A study of the companies’ practices demonstrated that inclusivity is increasingly penetrating their culture. The emergence and spread of inclusive leadership are largely in line with the needs of today’s soci ety, representing a link in regulating diversity and building sustainable management systems. From our analysis, we deduce that determining whether inclusive leadership is a distinct type of leadership is only possible with accumulation of practical experience and its academic systematization.